(untitled) (PERcursos Linguísticos, 2020)
This research is dedicated to the understanding of the mental representation of the grammatical and lexical aspect. More recent research on sentence formation, (Arad, 1996; Smith, 1997; Verkuyl, 2003; Wachowicz, 2006) has shown the close relationship between predicative structuring and the verbal aspect. It is understood currentlythat the lexical aspectual notions are directly linked to the predicate of the sentence and the items from the lexicon, which are called the syntactic-semantic lexical interface. From the minimalist point of view (Chomsky, 1995; Radford, 2004), this paper seeks to answer the following questions: how does the relation between internal arguments and preacher influence the formation of the lexical aspect? How is the representation of the grammatical and lexical aspects in the mental module? In addition to verbal and inflectional phrases, is there a need for an aspectual syntagm? After analyzing 320 statements taken from the NURC collection, and cross - referencing between verbal typology, internal arguments, grammatical and lexical aspects, in the Varbrul data program, this work suggests a syntactic structure with aspectual phrases, it is capable of covering the aspects grammatical and lexical expressions without distorting the minimalist assumptions. The structure is presented through tree representation with the aspectual phrases necessary to accommodate the traits coming from the lexicon.